Condições de trabalho e saúde de trabalhadores do Programa de Atenção em Saúde Mental de Feira De Santana-BA - Gomes, Décio de Jesus (2010)
The work in mental health raises important physical, psychic, biological, physiological, chemical and mechanical overloads on the health of the worker. However, there are limited epidemiological studies to characterize the working and health conditions of workers that work in multidisciplinary teams. This paper aimed to characterize the working and health conditions of workers from the Mental Health Attention Program in Feira de Santana-BA. This is an epidemiological cross-sectional descriptive census study, including employees from the Municipal Attention Program in Metal Health Care in Feira de Santana-BA. The data had been collected through self-administered questionnaire. The work characteristics, it was estimated the prevalence of common mental disorders, medicine consumption, alcohol abuse and smoking habits. The workers population from the Program is composed by 134 individuals; from these 81 had answered to the questionnaire but four of them were excluded because they were in service less than six months, thus remaining 77 respondents (response rate of 57.5%). Among the workers studied, 78.9% are female, the age average is 36 years,ranging from 23 up to 70 years old, married ones represent 43.4% of the total, followed by singles with 38.2%; 41 , 6% have a higher degree with pos graduation (specialization, master's or doctoring), followed by 32.5% of high school. The monthly average income is R$ 2.139,58, ranging from R$ 460, 00 up to R$ 12.000,00. The prevalence of common mental disorders is 29.6%, by alcohol abuse, 3.2%, 3.9% are smokers and 6.6% use sleep medication. It is considered that the joined data allow describing how the population of workers from the Attention Program in Mental Health Care is in Feira de Santana-BA, as well as identify the most significant aspects related to working conditions, health and lifestyles of workers, offering support for future studies on the theme. Moreover, it reveals the importance of extending new studies with similar methods to extract important information, comparable and generalized for this population.